2021
DOI: 10.1021/acs.jafc.0c07327
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Lactulose Ameliorates the Cognitive Deficit in Alzheimer’s Disease Mouse Model through Macroautophagy and Chaperone-Mediated Autophagy Pathways

Abstract: Lactulose, as a prebiotic, can be utilized by human gut microbiota and stimulate their growth. Although microbiota modulation has become an emerging approach to manage many diseases and can be achieved by the administration of prebiotics, fewer investigations have been carried out on the therapeutic mechanism of lactulose. Two trehalose analogs, lactulose and melibiose, were identified as having a neuroprotective effect in polyglutamine and Parkinson disease models. In this study, we examined lactulose and mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 105 publications
0
23
0
Order By: Relevance
“…Recently, the therapeutic mechanism of lactulose in AD has been uncovered. Lee et al (2021) found that pretreatment with lactulose can modulate the gut microbiome and insulin sensitivity, decrease neuroinflammation, and increase the levels of autophagy pathways. These findings suggest that the neuroprotective effect of lactulose is partially caused by autophagy activity.…”
Section: Prebioticsmentioning
confidence: 99%
“…Recently, the therapeutic mechanism of lactulose in AD has been uncovered. Lee et al (2021) found that pretreatment with lactulose can modulate the gut microbiome and insulin sensitivity, decrease neuroinflammation, and increase the levels of autophagy pathways. These findings suggest that the neuroprotective effect of lactulose is partially caused by autophagy activity.…”
Section: Prebioticsmentioning
confidence: 99%
“…This result suggests that trehalose and lactulose could be developed and optimized for the treatment or prevention of AD. 44 MAPT fragments, after being degraded by autophagy, can be a substrate of CMA by binding to HSC70 and entering the lysosome. 45 However, CMA dysfunction may lead to inefficient translocation of MAPT fragments, which potentiates MAPT aggregation, lysosomal dysfunction, and ultimately AD pathology.…”
Section: Adap Tive Autophagy In Admentioning
confidence: 99%
“…For example, yeast beta glucans administration to mouse models of AD proved effective in re-establishing the balance between pro-inflammatory and anti-inflammatory gut microbiome species, promoting SCFAs production and limiting neuroinflammation and insulin resistance [ 127 ]. Reduced neuroinflammation and improved short-term memory and cognitive ability in mice resembling AD features were also reported upon pre-treatment with lactulose and melibiose, two trehalose analogues, possibly via enhanced autophagy function [ 129 ]. Furthermore, 5xFAD mice fed for eight weeks with mannan oligosaccharide were shown capable of favoring the growth of Lactobacillus species and decreasing Helicobacter abundance, therefore preventing LPS leakage and intestinal epithelial barrier and BBB dysfunctions [ 130 ].…”
Section: Mainmentioning
confidence: 92%
“…A growing body of evidence suggests their potentiality as adjuvant therapy in different neurological and psychiatric conditions, such as anxiety, depression, and PD [ 126 ]. Recently, some studies are also considering the use of prebiotics for AD prevention/therapy, with promising results [ 124 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. For example, yeast beta glucans administration to mouse models of AD proved effective in re-establishing the balance between pro-inflammatory and anti-inflammatory gut microbiome species, promoting SCFAs production and limiting neuroinflammation and insulin resistance [ 127 ].…”
Section: Mainmentioning
confidence: 99%